Impact of Ethical Leadership on Employee Engagement: Role of Self-Efficacy and Organizational Commitment - Fouzia Ashfaq; Ghulam Abid; Sehrish Ilyas (MDPI AG, 2021)
The aim of this study was to examine the roles of self-efficacy and organizational commitment in the sequential mediation of the relationship between ethical leadership and employee engagement. Data were collected through self-reported questionnaires of employees from private and public sector organizations of Pakistan. We opted for a three-wave time-lagged design, and we used the PROCESS macro by Hayes on a sample of 211 employees (35% male, 65% female) via the 2000 re-sample bias-corrected bootstrap method. The results show a significant relationship between ethical leadership and employee engagement with mediating effects of self-efficacy and organizational commitment. Self-efficacy and organizational commitment fully mediated the relationship. The results provide insight into the understanding of employee behavior, particularly in the presence of moral leadership. Drawing on the conservation of resource theory, we examined how ethical leader support enables employees to invest their resources into positive outcomes. Theoretical and practical implications are discussed.